Thermoplastic cable shielding material and preparation method thereof

By using thermoplastic material preparation method in cable shielding materials and using multi-stage heating stirring and extrusion molding technology to form a uniform conductive network and a tight composite structure, the problem of insufficient shielding performance and mechanical strength of existing materials is solved, and the electromagnetic shielding performance and use stability of the material are significantly improved.

CN119775654APending Publication Date: 2025-04-08ANGREEN DONGGUAN NEW MATERIALS TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510058205.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing cable shielding materials have low shielding performance in high-frequency electromagnetic environments and insufficient tensile strength and toughness, which leads to the material being easily broken or peeled off, affecting the stability of long-term use.

Method used

A method for preparing thermoplastic cable shielding material is adopted, including drying and screening the conductive filler and the matrix resin, and then adding conductive filler, plasticizer and heat stabilizer to the volatile solution, and performing multi-stage heating and stirring and extrusion forming to form a uniform conductive network and a tight composite structure.

Benefits of technology

It significantly improves the electromagnetic shielding performance and mechanical strength of cable shielding materials, enhances the flexibility and dynamic load resistance of the material, reduces the risks of thermal aging and interface separation, and improves the long-term use stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775654A_ABST
    Figure CN119775654A_ABST
Patent Text Reader

Abstract

The invention provides a thermoplastic cable shielding material and a preparation method thereof.The preparation method comprises the steps that conductive filler and matrix resin are sequentially dried and screened, the matrix resin comprises at least one of polyethylene, polypropylene and polyurethane, and the conductive filler comprises at least one of conductive carbon black, graphite powder, tin-lead alloy and bismuth-tin alloy; adding matrix resin into the volatile solution, sequentially adding conductive filler, a plasticizer and a heat stabilizer, and uniformly stirring to obtain a pretreated suspension; the pretreatment suspension liquid is transferred into reaction equipment, multi-stage heating and stirring operation is carried out, a molten mixture is obtained, and the reaction equipment has a heating function and a stirring function; and adding a lubricant into the molten mixture, transferring into extrusion equipment, carrying out extrusion molding, and cooling to obtain the thermoplastic cable shielding material. The mixing uniformity is remarkably improved, a continuous conductive network can be formed in the material, the electromagnetic shielding performance is greatly improved, and the mechanical strength of the material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and in particular relates to a thermoplastic cable shielding material and a preparation method thereof. Background Art

[0002] Cable shielding materials are widely used in various fields from consumer electronics to aerospace due to their excellent conductivity, flexibility and environmental adaptability. With the rapid development of high-frequency communications, intelligent equipment and new energy technologies, their application scenarios will be further expanded, while placing higher requirements on material performance and manufacturing processes.

[0003] In the prior art, the cable shielding material is manufactured by mixing the matrix resin and the functional filler. However, during the mixing process, the difference in chemical properties between the matrix resin and the functional filler will lead to insufficient interface force, which will affect the dispersibility of the functional filler, resulting in a decrease in the electromagnetic shielding effect, and the signal interference cannot be effectively suppressed. The material shows low shielding performance in a high-frequency electromagnetic environment. On the other hand, due to the inadequacy of the processing technology, it is difficult to mix the functional filler and the matrix resin evenly in the molten state, resulting in stress concentration of the material, and the filler-rich area becomes a weak point. The tensile strength and toughness of the shielding material are low, and the cable shielding layer is easy to break or peel off, affecting the long-term stability. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a thermoplastic cable shielding material and a preparation method thereof, aiming to solve the problem of low shielding performance and mechanical strength of the cable shielding material.

[0005] In order to solve the above problems, the present invention provides a method for preparing a thermoplastic cable shielding material, the steps comprising: S1. Drying and screening the conductive filler and the matrix resin in sequence, wherein the matrix resin comprises at least one of polyethylene, polypropylene, and polyurethane, and the conductive filler comprises at least one of conductive carbon black, graphite powder, tin-lead alloy, and bismuth-tin alloy; S2, adding the base resin to the volatile solution, and then sequentially adding the conductive filler, plasticizer and thermal stabilizer, and stirring evenly to obtain a pre-treatment suspension; S3, transferring the pre-treated suspension to a reaction device, performing a multi-stage heating and stirring operation to obtain a molten mixture, wherein the reaction device has a heating function and a stirring function; S4, adding a lubricant to the molten mixture and transferring it to an extrusion device for extrusion molding, and obtaining a thermoplastic cable shielding material after cooling.

[0006] In some embodiments of the present invention, step S1 comprises: S1.1, respectively placing the resin raw material and the conductive raw material in a vacuum drying oven, drying them, and cooling them to obtain the matrix resin and the conductive filler, wherein the drying temperature is 70-90°C, and the drying time is 4-6 hours; S1.2. Using a vibrating screen, the base resin and the conductive filler are sieved to a particle size of less than 100 μm.

[0007] In some embodiments of the present invention, step S2 includes: S2.1, adding an organic solvent to a thermostatic stirrer, heating and stirring to obtain a prepared solvent, wherein the heating temperature is 40-60°C, and the stirring speed is 150-350 rpm; S2.2, performing surface activation treatment on the base resin and the conductive filler respectively to obtain a pretreated resin and a pretreated filler; S2.3, first slowly adding the pretreated resin into the prepared solvent, then introducing carbon dioxide atmosphere to a supercritical state, and then slowly adding the pretreated filler into the prepared solvent to obtain a mixed suspension; S2.4, adding a plasticizer and a heat stabilizer to the mixed suspension, stirring evenly to obtain a pre-treated suspension.

[0008] In some embodiments of the present invention, in the step S2.1, the prepared solvent includes a main solvent and an auxiliary solvent, the main solvent includes at least one of tetrahydrofuran, n-hexane, and dichloroethane, the auxiliary solvent includes at least one of isopropanol, ethanol, and trichloroethylene, and the volume ratio of the main solvent to the auxiliary solvent is 2~3:1.

[0009] In some embodiments of the present invention, in step S3, the heating temperature of the multi-stage heating and stirring operation includes at least three interval temperature rise values, and each of the interval temperature rise values ​​is in any range of 60~80℃, 100~140℃, and 160~200℃.

[0010] In some embodiments of the present invention, in step S4, the lubricant includes at least one of zinc stearate, ethylene bisstearamide, fatty acid ester, paraffin, polyethylene wax, microcrystalline wax, polytetrafluoroethylene powder, silicone oil, and modified fatty acid ester, and the volume ratio of the lubricant to the molten mixture is 0.05~1:100.

[0011] In some embodiments of the present invention, the plasticizer includes at least one of phthalate plasticizers, phosphate plasticizers, epoxy resin plasticizers, fatty acid ester plasticizers, ester plasticizers, vegetable oil plasticizers, phosphate esters, and polyol plasticizers; The heat stabilizer includes at least one of a calcium zinc stabilizer, a lead salt stabilizer, an organic tin stabilizer, a transition metal complex stabilizer, a phenolic antioxidant, and a silicate stabilizer.

[0012] The present invention discloses a thermoplastic cable shielding material, which is made by the preparation method of the thermoplastic cable shielding material as described above. The thermoplastic cable shielding material comprises a base resin, a conductive filler, a plasticizer and a heat stabilizer. Calculated by weight percentage, the conductive filler accounts for 15-25wt%, the plasticizer accounts for 2-5wt%, the heat stabilizer accounts for 0.1-2wt%, and the balance is the base resin.

[0013] Compared with the prior art, the thermoplastic cable shielding material and the preparation method thereof in the present invention have the following beneficial effects: The present invention provides a thermoplastic cable shielding material and a preparation method thereof, the steps comprising: drying and screening a conductive filler and a matrix resin in sequence, wherein the matrix resin comprises at least one of polyethylene, polypropylene and polyurethane, and the conductive filler comprises at least one of conductive carbon black, graphite powder, tin-lead alloy and bismuth-tin alloy; adding the matrix resin to a volatile solution, and then sequentially adding a conductive filler, a plasticizer and a heat stabilizer, stirring evenly to obtain a pre-treatment suspension; transferring the pre-treatment suspension to a reaction device, performing multi-stage heating and stirring operations to obtain a molten mixture, wherein the reaction device has heating and stirring functions; adding a lubricant to the molten mixture and transferring it to an extrusion device for extrusion molding, and cooling to obtain the thermoplastic cable shielding material.

[0014] Since the melting points of the matrix resin (polyethylene, polypropylene, polyurethane) and the conductive filler (such as tin-lead alloy, bismuth-tin alloy) are similar within a certain range (the melting point of the matrix resin is 120~170°C, while the melting points of tin-lead alloy and bismuth-tin alloy are about 140~160°C), the two can achieve synchronous softening during the heating and melting stage. During the melt mixing process, the conductive filler and the matrix resin enter the molten state at the same time, reducing the local filler deposition or matrix overheating decomposition caused by the difference in melting points, and significantly improving the mixing uniformity. The matrix resin and the conductive filler with similar melting points form a good interface bonding during the melting process, and the matrix resin coats the conductive filler in the molten state to promote the uniform dispersion of the conductive filler in the material. Since the conductive filler has good distribution in the matrix, it can form a continuous conductive network inside the material, greatly improving the electromagnetic shielding performance. The evenly distributed filler forms a tightly integrated composite structure with the matrix, reducing stress concentration points and enhancing the mechanical strength of the material. The addition of plasticizers and the auxiliary effect of lubricants enhance the flexibility of the material and significantly improve its dynamic load resistance. The addition and uniform distribution of heat stabilizers reduce the risk of thermal aging and interface separation during long-term use. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic flow chart of the method for preparing the thermoplastic cable shielding material according to Example 1 of the present invention. DETAILED DESCRIPTION

[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0017] The present invention provides a thermoplastic cable shielding material, which includes a matrix resin, a conductive filler, a plasticizer and a heat stabilizer. The matrix resin includes at least one of polyethylene, polypropylene and polyurethane, and the conductive filler includes at least one of conductive carbon black, graphite powder, tin-lead alloy and bismuth-tin alloy. Calculated by weight percentage, the conductive filler accounts for 15-25wt%, the plasticizer accounts for 2-5wt%, the heat stabilizer accounts for 0.1-2wt%, and the balance is the matrix resin.

[0018] Among them, the conductive filler can account for 15wt%, 20wt%, 25wt%, the plasticizer can account for 2wt%, 3wt%, 5wt%, and the thermal stabilizer can account for 0.1wt%, 0.5wt%, 2wt%.

[0019] Since the melting points of the matrix resin (polyethylene, polypropylene, polyurethane) and the conductive filler (such as tin-lead alloy, bismuth-tin alloy) are similar within a certain range (the melting point of the matrix resin is usually 120~170°C, while the melting points of tin-lead alloy and bismuth-tin alloy are about 140~160°C), the two can be softened synchronously during the heating and melting stage. During the melt mixing process, the conductive filler and the matrix resin enter the molten state at the same time, reducing the local filler deposition or matrix overheating decomposition caused by the difference in melting points, and significantly improving the mixing uniformity.

[0020] The matrix resin and conductive filler with similar melting points form a good interface bond during the melting process. The matrix resin covers the conductive filler in the molten state, promoting the uniform dispersion of the conductive filler in the material. Since the conductive filler has good distribution in the matrix, it can form a continuous conductive network inside the material, greatly improving the electromagnetic shielding performance.

[0021] In the present invention, the melting points of the matrix resin and the conductive filler are similar, which avoids the risk of thermal degradation caused by premature melting of the matrix resin or delayed melting of the conductive filler during material processing. The addition of a thermal stabilizer further enhances the anti-oxidation performance during high-temperature processing and prolongs the service life of the material.

[0022] The matching melting points of the matrix resin and the conductive filler make the fluidity of the molten material more stable, avoiding the agglomeration of the filler or the lack of matrix fluidity. The material can be efficiently processed in conventional single-screw or twin-screw extruders and is suitable for the molding of ribbon, sheet or tubular cable shielding materials.

[0023] Specifically, the plasticizer includes at least one of phthalate plasticizers, phosphate plasticizers, epoxy resin plasticizers, fatty acid ester plasticizers, ester plasticizers, vegetable oil plasticizers, phosphate esters and polyol plasticizers; the heat stabilizer includes at least one of calcium zinc stabilizer, lead salt stabilizer, organic tin stabilizer, transition metal complex stabilizer, phenolic antioxidant and silicate stabilizer.

[0024] Please refer to Figure 1 The present invention provides a preparation method for preparing a thermoplastic cable shielding material, the preparation method comprising the steps of: S1. Dry and screen the conductive filler and the matrix resin in sequence.

[0025] Step S1 includes: S1.1. Place the resin raw material and the conductive raw material in a vacuum drying oven respectively, dry them, and obtain the matrix resin and the conductive filler after cooling. The drying temperature is 70-90°C, for example, 70°C, 80°C, 90°C, and the drying time is 4-6h, for example, 4h, 5h, 6h.

[0026] The matrix resin and conductive filler are prone to absorb moisture during storage and transportation. Vacuum drying effectively removes moisture and avoids the following problems caused by residual moisture during processing: Bubble problem. The evaporation of moisture at high temperature may cause bubbles in the molten system, destroying the uniformity of the material and the conductive network. Reduced mechanical properties. Moisture may cause hydrolysis and degradation of the matrix resin, resulting in reduced mechanical properties of the material. Poor interface bonding. Moisture will form an isolation layer between the filler and the resin, affecting the dispersion of the filler and the interface bonding effect.

[0027] After drying, the surface of the conductive filler becomes drier and purer, which helps to evenly disperse the filler in the matrix resin. This provides a good foundation for the subsequent conductive network formation. Drying in a vacuum environment reduces the contact of the filler and resin with oxygen at high temperatures, avoids possible oxidation or degradation reactions, and ensures the chemical stability of the material.

[0028] S1.2. Use a vibrating screen to sieve the base resin and the conductive filler to a particle size of less than 100 μm.

[0029] Screening controls the base resin and conductive filler within a similar particle size range, avoiding the following problems caused by large differences in particle size: Filler sedimentation. Conductive fillers with larger particle sizes tend to settle during the melt mixing process, resulting in uneven conductivity of the material. Difficulty in dispersion. Fillers with too small particle sizes may aggregate during the mixing process to form agglomerates, affecting the performance of the material. Improve mixing uniformity. Base resins and conductive fillers with similar particle sizes are more likely to form a uniform distribution during the subsequent melt mixing process, significantly improving the processing performance and final performance of the material. Improve conductivity. Uniform filler particle size makes it easier for conductive fillers to form a continuous conductive network in the base resin, further improving the conductivity and shielding effect of the material. Optimize extrusion processability. The fluidity of the material after screening is more stable. Resin particles and fillers with uniform particle sizes help avoid blockage or instability during extrusion, improving the efficiency of the extrusion process and product quality.

[0030] The particle size of carbon black and graphite powder can be kept within a certain range through screening and processing to avoid filler stratification caused by excessive particle size differences. A reasonable particle size range helps the two fillers to be evenly dispersed in the matrix resin at the same time, improving the mixing uniformity, thereby greatly improving the electromagnetic shielding performance and enhancing the mechanical strength of the material.

[0031] The conductive carbon black is 50~200nm, for example, 50nm, 100nm, 200nm. The particles are small enough to provide a large specific surface area and form a conductive network. Too small particle size (<50nm) may cause agglomeration, which is not conducive to dispersion.

[0032] The graphite powder is 2~10μm, for example, 2μm, 5μm, 10μm. Micron-sized particles are easy to maintain uniform distribution in the resin matrix. Too large particle size (>10μm) is easy to settle or affect the shielding performance, while too small particle size (<2μm) will increase the surface energy and cause agglomeration.

[0033] S2. Add the base resin into the volatile solution, and then add the conductive filler, plasticizer and thermal stabilizer in sequence, and stir evenly to obtain a pre-treatment suspension.

[0034] Step S2 includes: S2.1. Add an organic solvent to a thermostatic stirrer, heat and stir to obtain a prepared solvent, wherein the heating temperature is 40-60°C, for example, 40°C, 50°C, 60°C, and the stirring speed is 150-350 rpm, for example, 150 rpm, 200 rpm, 350 rpm.

[0035] The preparation solvent includes a main solvent and an auxiliary solvent, the main solvent includes at least one of tetrahydrofuran, n-hexane, and dichloroethane, the auxiliary solvent includes at least one of isopropanol, ethanol, and trichloroethylene, and the volume ratio of the main solvent to the auxiliary solvent is 2~3:1, for example, it can be 2:1, 2.5:1, or 3:1.

[0036] The main solvent has a high dissolving power and has excellent swelling and dissolving effects on the matrix resin (such as polyethylene, polypropylene, and polyurethane). Among them, tetrahydrofuran (THF) has a strong polarity and is suitable for dissolving polar resins (such as polyurethane). It can accelerate the molecular chain expansion of the matrix resin to form a uniform solution. Hexane is non-polar and suitable for dissolving non-polar resins (such as polyethylene and polypropylene). It has good fluidity and is easy to mix and disperse in the subsequent process. Ethylene dichloride has a medium polarity and strong compatibility. It can dissolve polar and non-polar resins, quickly wet the resin particles, and promote the uniform swelling of the matrix.

[0037] Auxiliary solvents play a role in adjusting the viscosity of the solution and expanding the polarity range of the solvent. Among them, isopropyl alcohol (IPA) has a medium polarity, which helps improve the dispersibility and volatility of the main solvent, and can be evenly distributed at the interface between the matrix resin and the filler to avoid excessive local concentration. Ethanol has a weak polarity and good fluidity, which reduces the viscosity of the mixed system and evaporates quickly, which helps to improve the uniformity of the solution. Trichloroethylene has a moderate polarity and has excellent wetting and dispersing effects on conductive fillers (such as carbon black and graphite powder).

[0038] The main solvent has a high penetration ability and can penetrate into the microscopic pores of the conductive filler particles to enhance wettability. The auxiliary solvent (such as trichloroethylene) reduces the viscosity of the solution and helps the filler particles to be more evenly dispersed in the solution. The high solubility of the main solvent and the good diffusivity of the auxiliary solvent work together to effectively reduce the agglomeration of the conductive filler. The mixed solvent system optimizes the interfacial wettability of the filler and the matrix resin, promotes the improvement of the interfacial bonding force, and lays the foundation for the formation of the conductive network.

[0039] The difference in boiling points between the main solvent and the auxiliary solvent (e.g., THF has a boiling point of 66°C and isopropanol has a boiling point of 82.5°C) allows the solvent to evaporate gradually, forming a smooth solution concentration gradient, avoiding the problem of solution instability and precipitation caused by rapid evaporation. The main solvent evaporates first, and the auxiliary solvent continues its dissolving effect to ensure the stability of the suspension.

[0040] When heated, the molecular motion of organic solvents intensifies, and their solubility in matrix resins is significantly improved. The temperature is controlled at 40~60℃ to avoid excessive temperature causing rapid evaporation of volatile solvents or thermal degradation of matrix resins. The combination of constant temperature and stirring speed makes the temperature and concentration distribution of the solvent more uniform, avoiding local oversaturation or thermal gradients. The uniformly formulated solvent provides a stable suspension medium for matrix resins, conductive fillers, plasticizers and thermal stabilizers.

[0041] S2.2, performing surface activation treatment on the base resin and the conductive filler respectively to obtain pretreated resin and pretreated filler.

[0042] Surface activation treatment changes the surface properties of the matrix resin and conductive filler (such as hydroxylation or carboxylation), increasing their surface energy, thereby improving their dispersibility and affinity in the solution. After the conductive filler surface is activated, the interfacial bonding force with the matrix resin is enhanced, and the conductive network formation is more stable. Surface activation of carbon black or graphite powder can increase polar functional groups, which helps to interact with polar plasticizers or thermal stabilizers. Surface activation reduces the tendency of fillers to agglomerate in solution by destroying the van der Waals force between filler particles, thereby improving mixing uniformity.

[0043] The matrix resin (such as polyethylene, polypropylene, polyurethane) is a polymer material, which is difficult to form a good interface with other components (such as conductive fillers). Therefore, the following surface activation treatment method is required to improve its surface energy and interface compatibility.

[0044] (1) Plasma treatment: Plasma physically bombards and chemically reacts on the surface of the base resin to introduce polar groups (such as hydroxyl, carbonyl, and carboxyl).

[0045] Oxygen, nitrogen or air is introduced for plasma activation treatment for 30 to 300 seconds, such as 30 seconds, 60 seconds, 100 seconds, or 300 seconds, with a power of 10 to 100 W, such as 10 W, 50 W, or 100 W.

[0046] Through plasma activation treatment, the surface polarity can be increased, the bonding force with the conductive filler can be improved, the substrate surface can be more easily wetted, and the uniformity of subsequent mixing can be improved. For the conductive filler, plasma treatment can also be performed, which will not be described in detail here.

[0047] (2) Chemical grafting modification: using oxidants or initiators (such as potassium persulfate, benzoyl peroxide) to graft monomers containing polar groups (such as acrylic acid, methacrylic acid) onto the surface of the substrate.

[0048] The reaction temperature is 60-90°C, for example, 60°C, 70°C, 90°C, and the reaction time is 30-60min, for example, 30min, 40min, 60min. The interface polarity can be significantly improved, the adhesion between the matrix resin and the filler can be promoted, and the mechanical strength and stability of the material can be enhanced.

[0049] (3) Ultraviolet light (UV) treatment: High-energy ultraviolet light irradiates the surface of the substrate to produce free radicals and oxidation, generating functional groups such as hydroxyl and carboxyl.

[0050] The wavelength of ultraviolet light used is 240-280nm, for example, 240nm, 250nm, 260nm, and the treatment time is 1-10min, for example, 1min, 5min, 10min, which can enhance the activity of the substrate surface and the binding ability of the filler and improve the interface performance of the material.

[0051] The surface of conductive fillers (such as conductive carbon black, graphite powder, tin-lead alloy, bismuth-tin alloy) is easy to adsorb impurities or oxide layers, which may cause filler agglomeration or poor interface bonding. Therefore, surface activation treatment is required through the following methods: (1) Surface pickling: Use a strong acid solution (such as nitric acid or sulfuric acid) to remove oxides or impurities on the surface of the filler to expose a fresh surface.

[0052] The acid used can be 5-10% nitric acid, 5-20% sulfuric acid, etc., and the pickling time is 10-30 minutes, for example, 10 minutes, 20 minutes, 30 minutes. Pickling can remove the oxide layer, enhance the conductivity and interface bonding ability, improve the dispersion of fillers, and reduce agglomeration.

[0053] (2) Coupling agent treatment: Use coupling agents (such as silane coupling agents, titanate coupling agents) to form chemical bonds or physical adsorption layers on the filler surface to enhance the compatibility between the filler and the matrix.

[0054] The concentration of the coupling agent is 0.5-2.0wt%, for example, 0.5wt%, 1wt%, 2wt%, and the conductive filler and the coupling agent are placed in a solvent, which can be ethanol or water, and the treatment time is 1-2h, for example, 1h, 1.5h, 2h. The coupling agent treatment can enhance the dispersibility of the filler and the bonding force with the matrix, and improve the uniform distribution of the filler in the mixture.

[0055] (3) Heat treatment: Heat the filler surface at high temperature to remove adsorbed water and volatile impurities.

[0056] The heating temperature is 300-500°C, for example, 300°C, 400°C, 500°C, and the heating time is 2-4h, for example, 2h, 3h, 4h. Heat treatment can remove impurities and adsorbed gases, increase the surface activity of the filler, and enhance the conductivity and thermal stability.

[0057] S2.3, first slowly add the pretreated resin into the prepared solvent, then introduce carbon dioxide atmosphere to a supercritical state, and then slowly add the pretreated filler into the prepared solvent to obtain a mixed suspension.

[0058] Slowly add the pre-treated resin to the preparation solvent to avoid adding it all at once, which may cause local oversaturation or uneven solution. The preparation solvent can completely swell or dissolve the matrix resin through efficient dissolution to form a uniform matrix solution.

[0059] The pre-treated filler is slowly added to the formulation solvent under supercritical carbon dioxide to effectively avoid filler agglomeration. The low viscosity and high permeability of carbon dioxide enhance the fluidity and uniform distribution of the filler in the system. The gradual addition of resin and filler reduces the viscosity variation of the system, making the mixing process easier to control.

[0060] Supercritical carbon dioxide has a liquid-like solubility and a gas-like high diffusivity, which can fully penetrate the surface of the matrix resin and filler, further promoting the interfacial interaction between the two. Under the action of carbon dioxide, the surface of the filler particles forms a closer contact with the matrix resin, which is conducive to interfacial bonding.

[0061] Through the mediation of supercritical carbon dioxide, the affinity between the filler surface and the matrix resin is improved, reducing delamination or performance degradation caused by incompatibility.

[0062] Slowly add fillers, combined with the effect of supercritical carbon dioxide, to evenly distribute the fillers in the matrix solution, avoiding particle aggregation or sedimentation. Supercritical carbon dioxide reduces the viscosity of the solution and improves the dispersibility and suspension stability of the filler particles in the system. It provides a stable premixed state for subsequent melt mixing or extrusion molding, reducing the complexity of subsequent processes.

[0063] The filler is fully dispersed in the matrix under supercritical carbon dioxide environment, providing a good foundation for the formation of a continuous conductive network. The uniform filler distribution makes the contact between the conductive particles more complete, which helps to improve the electromagnetic shielding performance and conductivity of the material.

[0064] Supercritical carbon dioxide technology reduces the reliance on high-temperature heating and achieves efficient dissolution and dispersion at low temperatures. After the process is completed, carbon dioxide can be quickly gasified by decompression without producing solvent residues, meeting the requirements of green processing.

[0065] The operating conditions of supercritical carbon dioxide (such as pressure and temperature) can be adjusted according to the characteristics of the matrix resin and filler to adapt to a variety of material systems.

[0066] S2.4. Add plasticizer and heat stabilizer to the mixed suspension, stir evenly to obtain a pre-treated suspension.

[0067] Plasticizers can lower the glass transition temperature and melt viscosity of the base resin, making the material more flexible, enabling low-temperature processing, and reducing energy consumption and equipment wear.

[0068] Plasticizers make the molten state of the mixed system more fluid and the filler more evenly dispersed, which helps the subsequent extrusion molding, prevents the melt from adhering to the inner wall of the processing equipment, improves the processing smoothness, improves the processing adaptability of the highly filled system, and avoids local overheating or melt fracture.

[0069] Thermal stabilizers can capture free radicals and decompose peroxides during high-temperature processing, avoiding oxidative degradation of the matrix resin, reducing the degradation of mechanical properties caused by high temperature, and extending the service life of the material. Conductive fillers may oxidize at high temperatures, resulting in a decrease in conductivity. The addition of thermal stabilizers can protect the filler surface, maintain its chemical stability, prevent yellowing and embrittlement of the molten system, and improve the weather resistance and long-term performance of the material. The protective effect of thermal stabilizers prevents the conductive filler from degrading due to oxidation or high temperature, ensuring its stability during use.

[0070] Plasticizers can reduce the viscosity of the suspension, making the conductive filler (such as carbon black, graphite powder) more evenly dispersed in the matrix resin, reducing the agglomeration of filler particles, and forming a more stable mixed system. The synergistic effect of heat stabilizers and plasticizers enhances the compatibility of the matrix resin and filler interface, which helps to form a conductive network. Plasticizers can also improve the dispersibility of fillers, making filler particles easier to contact and arrange, forming a continuous conductive path, significantly improving the conductive performance, and enhancing the electromagnetic shielding performance of the material.

[0071] The role of plasticizers reduces the amount of solvents used and reduces the residual volatile organic matter in the material. The addition of heat stabilizers avoids increased energy consumption and material loss caused by material degradation during high-temperature processing.

[0072] Under stirring conditions, plasticizers and thermal stabilizers can be evenly distributed in the mixed suspension, ensuring the uniformity of material components, reducing the uncertainty of subsequent mixing and processing, and improving the batch consistency and controllability of the material.

[0073] S3, transferring the pre-treated suspension to a reaction device, performing a multi-stage heating and stirring operation to obtain a molten mixture, wherein the reaction device has a heating function and a stirring function.

[0074] In step S3, the heating temperature of the multi-stage heating and stirring operation includes at least three interval temperature rise values, and each interval temperature rise value is in any range of 60-80°C, 100-140°C, and 160-200°C.

[0075] In step S3, a multi-stage heating and stirring operation is performed to gradually increase the heating temperature and combine the stirring operation to ensure that the pre-treated suspension is converted into a uniform molten mixture.

[0076] In the first temperature zone (60~80℃), at a relatively low temperature, the initial volatilization of the solvent is controlled to avoid the formation of bubbles caused by rapid volatilization. The matrix resin (such as polyethylene, polypropylene, polyurethane) begins to soften or swell, avoiding the phenomenon that the outer layer melts while the inner layer does not melt due to rapid temperature rise, making the resin melt more uniform. The partial volatilization of the solvent gradually exposes and wets the filler surface, and the interaction force between the filler particles (such as van der Waals force) is weakened.

[0077] In the second temperature zone (100~140℃), the remaining solvent gradually evaporates, and the bubbles in the suspension are gradually released to form a uniform molten system. The resin enters the molten state, and the molecular chains begin to flow, providing a good matrix environment for the dispersion of the filler. The filler is fully contacted with the resin and initially dispersed, and the stirring action further breaks up the filler agglomerates.

[0078] The third temperature zone (160~200℃) keeps the resin completely melted and the fluidity reaches the best state, which is conducive to the final uniform dispersion of the filler and the formation of the conductive network. The filler is evenly distributed in the molten resin to form a stable suspension state.

[0079] Through staged temperature control, the agglomeration of conductive fillers (such as graphite powder, carbon black, tin-lead alloy) is reduced, local overheating or degradation of the resin is reduced, the mechanical properties and chemical stability of the resin are maintained, the fluidity of the resin melt is improved, and the foundation is laid for subsequent mixing and molding. The filler is evenly distributed in the matrix, and the conductive properties and shielding effect of the material are improved.

[0080] In different temperature zones, the fillers gradually disperse and contact, and through stirring and the action of molten resin, a continuous conductive path is spontaneously formed. In the high temperature zone (160~200℃), the contact resistance between filler particles is further reduced, and the conductive performance is enhanced. The conductive network is more evenly distributed, improving the electromagnetic shielding performance and enhancing the stability and consistency of the conductive material.

[0081] Plasticizers and heat stabilizers are prone to decomposition at high temperatures. Multi-stage heating can be used to prevent them from being directly exposed to high temperature environments and prolong their effectiveness. Gradually increasing the temperature allows the plasticizers and heat stabilizers to be fully mixed into the matrix and fillers to improve their effectiveness. Avoiding oxidation or degradation of the matrix resin or fillers due to overheating can maintain material properties. The heat stabilizer is more evenly distributed, improving the thermal stability and long-term performance of the material.

[0082] S4, adding a lubricant to the molten mixture and transferring it to an extrusion device for extrusion molding, and obtaining a thermoplastic cable shielding material after cooling. In step S4, the lubricant includes at least one of zinc stearate, ethylene bis stearamide, fatty acid ester, paraffin, polyethylene wax, microcrystalline wax, polytetrafluoroethylene powder, silicone oil, and modified fatty acid ester, and the volume ratio of the lubricant to the molten mixture is 0.05 to 1:100, for example, 0.05:100, 0.1:100, and 1:100.

[0083] Lubricants are distributed between the molecules of the matrix resin, reducing the internal friction between the molecular chains and improving the fluidity of the material. They make the melt flow more smoothly in the extrusion equipment and avoid melt fracture or blockage. Lubricants form a lubricating layer between the molten mixture and the extrusion equipment, reducing the friction coefficient and alleviating equipment wear.

[0084] The extrusion speed is increased, the material flows more smoothly in the equipment, the material will not be locally overheated due to the accumulation of frictional heat, the stability of the extrusion process is improved, the wear of the equipment screw and barrel is reduced, and the service life of the equipment is extended.

[0085] The lubricant is evenly distributed in the molten mixture, reducing the adhesion between the melt and the mold, and plays a role in separation and smoothing during the extrusion process, making the surface of the material smoother and smoother. The surface of the cable shielding material has no obvious defects or textures, which improves the aesthetics. The lubricating effect avoids deformation caused by uneven resistance during the extrusion of the material and ensures dimensional consistency. The lubricant reduces the viscosity of the molten mixture and enhances the dispersibility of the conductive filler (such as conductive carbon black and graphite powder). The lubricant forms a lubricating layer on the surface of the conductive filler, reducing the agglomeration of the filler. The conductive filler is more evenly dispersed in the matrix resin to avoid local aggregation. After the filler is evenly dispersed, the conductive particles are easier to contact, forming a continuous conductive path, improving the conductivity and shielding performance of the material.

[0086] Lubricants reduce the interfacial resistance between fillers, making it easier for conductive filler particles to contact and align. They optimize the distribution of fillers in the matrix, provide a more stable environment for the formation of a conductive network, form a more efficient conductive network, reduce resistivity, and improve electromagnetic shielding performance. Lubricants protect the surface of fillers to prevent the degradation of conductive properties due to oxidation or stress.

[0087] Lubricants reduce frictional heat during high-temperature extrusion to prevent degradation of the base resin or filler due to overheating. Some lubricants (such as silicone oil and polytetrafluoroethylene powder) have good thermal stability and can remain chemically inert at high temperatures, preventing the base resin from degrading its mechanical properties due to high-temperature oxidation or degradation. Heat-sensitive components (such as plasticizers and fillers) are protected and material properties remain stable.

[0088] The lubricant interacts with the molecular chain of the matrix resin, reduces the friction between the chain segments, improves the flexibility of the material, improves the stress distribution during the extrusion molding process, and reduces the internal stress of the material. The bending and tensile properties of the material are enhanced, which is suitable for cable bending or complex application environments. After extrusion, the internal stress of the material is reduced, avoiding cracking or peeling during long-term use.

[0089] The volume ratio of lubricant to molten mixture is controlled at 0.05~1:100, and the dosage is extremely low, which neither significantly increases production costs nor causes significant pollution to the environment. Lubricants such as silicone oil and polytetrafluoroethylene powder have low volatility during processing and meet environmental protection requirements. Reduce the impact on the environment and improve the environmental performance of the product. Low lubricant dosage reduces raw material costs, while extending the service life of the equipment and indirectly reducing maintenance costs.

[0090] The specific structures of various mechanical devices used in the present invention, such as extrusion equipment, stirring equipment, reaction container, reaction device, etc., are known to those skilled in the art and will not be described in detail here.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a thermoplastic cable shielding material, characterized in that the steps include: S1. Drying and screening the conductive filler and the matrix resin in sequence, wherein the matrix resin comprises at least one of polyethylene, polypropylene, and polyurethane, and the conductive filler comprises at least one of conductive carbon black, graphite powder, tin-lead alloy, and bismuth-tin alloy; S2, adding the base resin to the volatile solution, and then sequentially adding the conductive filler, plasticizer and thermal stabilizer, and stirring evenly to obtain a pre-treatment suspension; S3, transferring the pre-treated suspension to a reaction device, performing a multi-stage heating and stirring operation to obtain a molten mixture, wherein the reaction device has a heating function and a stirring function; S4, adding a lubricant to the molten mixture and transferring it to an extrusion device for extrusion molding, and obtaining a thermoplastic cable shielding material after cooling.

2. The method for preparing a thermoplastic cable shielding material according to claim 1, characterized in that: The step S1 comprises: S1.1, respectively placing the resin raw material and the conductive raw material in a vacuum drying oven, drying them, and cooling them to obtain the matrix resin and the conductive filler, wherein the drying temperature is 70-90°C, and the drying time is 4-6 hours; S1.

2. Using a vibrating screen, the base resin and the conductive filler are sieved to a particle size of less than 100 μm.

3. The method for preparing a thermoplastic cable shielding material according to claim 2, characterized in that: The step S2 comprises: S2.1, adding an organic solvent to a thermostatic stirrer, heating and stirring to obtain a prepared solvent, wherein the heating temperature is 40-60°C, and the stirring speed is 150-350 rpm; S2.2, performing surface activation treatment on the base resin and the conductive filler respectively to obtain a pretreated resin and a pretreated filler; S2.3, first slowly adding the pretreated resin into the prepared solvent, then introducing carbon dioxide atmosphere to a supercritical state, and then slowly adding the pretreated filler into the prepared solvent to obtain a mixed suspension; S2.4, adding a plasticizer and a heat stabilizer to the mixed suspension, stirring evenly to obtain a pre-treated suspension.

4. The method for preparing a thermoplastic cable shielding material according to claim 3, characterized in that: In the step S2.1, the prepared solvent includes a main solvent and an auxiliary solvent, the main solvent includes at least one of tetrahydrofuran, n-hexane, and dichloroethane, the auxiliary solvent includes at least one of isopropanol, ethanol, and trichloroethylene, and the volume ratio of the main solvent to the auxiliary solvent is 2~3:

1.

5. The method for preparing a thermoplastic cable shielding material according to claim 1, characterized in that: In the step S3, the heating temperature of the multi-stage heating and stirring operation includes at least three interval temperature rise values, and each of the interval temperature rise values ​​is in any range of 60-80°C, 100-140°C, and 160-200°C.

6. The method for preparing a thermoplastic cable shielding material according to claim 1, characterized in that: In step S4, the lubricant includes at least one of zinc stearate, ethylene bisstearamide, fatty acid ester, paraffin, polyethylene wax, microcrystalline wax, polytetrafluoroethylene powder, silicone oil, and modified fatty acid ester, and the volume ratio of the lubricant to the molten mixture is 0.05~1:

100.

7. The method for preparing a thermoplastic cable shielding material according to claim 1, characterized in that: The plasticizer includes at least one of phthalate plasticizers, phosphate plasticizers, epoxy resin plasticizers, fatty acid ester plasticizers, ester plasticizers, vegetable oil plasticizers, phosphate esters and polyol plasticizers; The heat stabilizer includes at least one of a calcium zinc stabilizer, a lead salt stabilizer, an organic tin stabilizer, a transition metal complex stabilizer, a phenolic antioxidant, and a silicate stabilizer.

8. A thermoplastic cable shielding material, characterized in that: The thermoplastic cable shielding material is made by the preparation method of the thermoplastic cable shielding material according to any one of claims 1 to 7, wherein the thermoplastic cable shielding material comprises a base resin, a conductive filler, a plasticizer and a thermal stabilizer, and calculated by weight percentage, the conductive filler accounts for 15-25wt%, the plasticizer accounts for 2-5wt%, the thermal stabilizer accounts for 0.1-2wt%, and the balance is the base resin.

Citation Information

Patent Citations

  • Copolymer of grafting maleic anhydride on molten polypropylene and preparation method for copolymer

    CN102321217A

  • Polymer-based electromagnetic shielding material based on carbon fiber and graphene and preparation method of polymer-based electromagnetic shielding material

    CN104419107A

  • Method for modifying mineral filler

    CN104945660A

  • Preparation method of graphene power cable shielding layer

    CN108456359A

  • Graphene / macromolecular conductive composite material and preparation method thereof

    CN110305416A